Oral Cancer 2012
DOI: 10.5772/30520
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Oral Cancer

Abstract: up to 5% however has been reported for the United States (Batsakis, 1979), and higher rates have been reported for the so-called "high risk" areas of Europe with incidence equally varying with different socioeconomic groups within these areas (Johnson, 1991). Worldwide, it is estimated that about 300,000 people will be diagnosed with oral cancer in 2010 (Jemal et al., 2010). Of these, 126,000 will die from the disease (Jemal et al., 2010). In the United States alone, an estimated 35,000 new cases of oral cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…This is comparable to a projected total of 35,540 new oral cavity and pharynx cases and 1,529,560 total new cancer cases (approximately 2.3%) in the United States in 2010 (17). Oral cavity and pharynx related deaths in the United States were predicted to be approximately 1.4% of all cancer related deaths in 2010 (17), with SCC arising from oral mucosal lining accounting for over 90% of tumors (18)(19)(20).…”
Section: Discussionmentioning
confidence: 68%
“…This is comparable to a projected total of 35,540 new oral cavity and pharynx cases and 1,529,560 total new cancer cases (approximately 2.3%) in the United States in 2010 (17). Oral cavity and pharynx related deaths in the United States were predicted to be approximately 1.4% of all cancer related deaths in 2010 (17), with SCC arising from oral mucosal lining accounting for over 90% of tumors (18)(19)(20).…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have used serum level of Vitamin D as a useful biomarker and predictor for Cancer. Other studies reported in the literature have shown that OSCC has a receptor for Vitamin D known as the VDR (Vitamin D receptor) [ 6 , 7 , 8 & 9 ]. Osafi et al in an in vitro study suggested activation of two apoptotic pathways (caspase and bcl:bax) by Vitamin D as responsible for its anti-OSCC effects [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco cigarettes contain benzopyrene and nitrosamines, which are carcinogenic and result in DNA mutations when exposed to human cells. 13,15,16 Oral cancer, also known as oral squamous cell carcinoma (OSCC), is a malignant tumour that develops on the lips and oral cavity. OSCC cancers, which target the epithelial cells of the oral cavity and oropharynx, contribute to 90% of all oral cancers.…”
Section: Oral Cancermentioning
confidence: 99%